Winner Software - Make Your Very Own Virtual World With Olive. - Kushner, D. (IEEE spectrum)
Forterra's OLIVE software makes the business of virtual-world environments real. OLIVE creates virtual worlds for customers in health care, the military, and the media. One main difference between an OLIVE world and other virtual worlds is the OLIVE world's "purpose-driven" intent. Rather than make the kind of free-form environment found in EverQuest, OLIVE's customers want worlds that impart particular skills-like dealing with irate customers or safely disposing of bombs. The designers worked hard to give OLIVE's avatars-the computer-generated characters-gestures and inflections that are natural enough to fully involve users in the world. The ultimate goal is to create a persistent avatar-that is, one that can move seamlessly through a sea of interconnected virtual worlds.